Competitive Advantage in Mediating The Effect of Financial Flexibility on Financial Performance: Indonesian Sharia Stock Index - Hasyim, Diana; Budiarta, Kustoro (School of Business, Bogor Agricultural University (SB-IPB), 2023)
Resources are considered a key driver of organizational performance. However, the means to improve performance through resources remains an issue that is yet to be conclusively addressed in both theoretical and practical terms. This study aims to examine the roles of competitive advantage and Islamic Label (IL) in the relationship between financial flexibility and the performance of companies listed on the Indonesian Sharia Stock Index (ISSI). Using a longitudinal approach covering the period 2012–2021 and observing 88 companies, a total of 880 observations were obtained for this study. The statistical technique used for the analysis was variance-based structural equation modeling utilizing partial least squares with the statistical tool of WarpPLS. The study revealed that competitive advantage is able to partially mediate the impact of financial flexibility on firm performance. Proxies of competitive advantage, such as receivable turnover and financial leverage, were found to be significant to all performance proxies, namely ROA, ROE, and Tobin’s Q. However, IL did not significantly enhance the link between financial flexibility and performance. It was found that the mediating impact of competitive advantage on the relationship between financial flexibility and performance indicated that improving performance through financial flexibility is indirect. Thus, contingency factors should be given due consideration in enhancing resource-based performance. For Islamic label companies, competitive advantage can be built to enhance performance by optimizing resource utilization. Keywords: competitive advantage, contingency factors, financial flexibility, financial performance, Islamic label